2022
DOI: 10.3390/medsci10020028
|View full text |Cite
|
Sign up to set email alerts
|

Difluoromethylornithine (DFMO) Enhances the Cytotoxicity of PARP Inhibition in Ovarian Cancer Cells

Abstract: Ovarian cancer accounts for 3% of the total cancers in women, yet it is the fifth leading cause of cancer deaths among women. The BRCA1/2 germline and somatic mutations confer a deficiency of the homologous recombination (HR) repair pathway. Inhibitors of poly (ADP-ribose) polymerase (PARP), another important component of DNA damage repair, are somewhat effective in BRCA1/2 mutant tumors. However, ovarian cancers often reacquire functional BRCA and develop resistance to PARP inhibitors. Polyamines have been re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 76 publications
0
1
0
Order By: Relevance
“…Simultaneous exposure of ovarian cancer cells to DFMO and rucaparib (PARP inhibitor) inhibited polyamine synthesis and PARP activity, thereby enhancing the killing effect of cisplatin on ovarian cancer cells. These findings suggest that DFMO can be used as an adjuvant chemotherapeutic agent in the treatment of ovarian cancer [89].…”
Section: Dfmo-targeted Inhibition Of Odc For the Treatment Of Ovarian...mentioning
confidence: 78%
“…Simultaneous exposure of ovarian cancer cells to DFMO and rucaparib (PARP inhibitor) inhibited polyamine synthesis and PARP activity, thereby enhancing the killing effect of cisplatin on ovarian cancer cells. These findings suggest that DFMO can be used as an adjuvant chemotherapeutic agent in the treatment of ovarian cancer [89].…”
Section: Dfmo-targeted Inhibition Of Odc For the Treatment Of Ovarian...mentioning
confidence: 78%
“…DFMO acts as a suicide inhibitor of the first rate-limiting enzyme in polyamine biosynthesis, ornithine decarboxylase (ODC), thereby limiting intracellular polyamine concentrations. In a research article by El Naggar and colleagues [ 7 ], DFMO is demonstrated to improve the response of ovarian cancer cells to the PARP inhibitor rucaparib by increasing chemotherapy-mediated DNA damage. Considering the well-established clinical safety profile of DFMO, the inclusion of polyamine-blocking therapy as an adjunct to chemotherapy in ovarian cancer should be considered.…”
mentioning
confidence: 99%